Behavioral responses to wildfire smoke: Insights from smartphone location data - Clara Berestycki; M. Keith Chen (Proceedings of the National Academy of Sciences, 2026)
Although wildfire smoke is a major public health concern, relatively little is known about individual avoidance behavior. In this paper, we use smartphone-location data to study behavioral responses to smoke during the 2018 California wildfire season, one of the deadliest in recent US history. Using individual-level data, we construct daily measures of when and where California residents spend their time. We find that high levels of smoke increase time spent at home and indoors, while decreasing mobility and time at work. However, we find adaptation starts at relatively high levels of smoke—significantly higher than when smoke becomes dangerous—suggesting a gap between the levels of smoke that trigger adaptation and those that are harmful to human health. While we observe broad-based responses across most demographics, we find much stronger responses among high-SES residents, driven primarily by differences in education rather than income or other characteristics. We compare responses to smoke to those of rainfall, another disamenity to time outside whose costs are more obvious and immediate. While time at home and indoors increases with rain, these responses do not display the same socioeconomic gradient as smoke. Taken together, our results suggest that differential responses by education are unlikely to reflect differences in ability to adjust time and activities. Instead, they likely arise from differences in awareness of the health risks associated with wildfire smoke exposure.